SECONDARY SCHOOL PHYSICAL EDUCATION TEACHERS AND FOOTBALL COACHES' OPINIONS ON THE ROLE OF GAMES IN LEARNING FOOTBALL − SPECIFIC TACTICAL RELATIONSHIPS - Ionuț Alexandru BUDA; Carmen Maria ȚÎRU; Sorin BRÎNDESCU (Universitaria Publishing House, Craiova, 2022)
The game is seen as a teaching method by which tactical relationships are learned with more enjoyment and gradually replaces the traditional way of teaching motor skills. This study aims to determine the opinion of physical education and sports teachers/ football coaches about the impact of the games on the learning of football-specific tactical relationships. To achieve the intended purpose, we conducted quantitative research with a non-experimental design, the study being descriptive. The participants completed a questionnaire containing 12 items regarding their opinion on the impact of the games on the learning of footballspecific tactical relationships. The sample was represented by 25 people, 12 football coaches, and 13 physical education and sports teachers. The study found that secondary school sports teachers and football coaches positively approve of the game's role in learning football-specific tactical relationships. The results showed significant differences between them only on specific dimensions considered.